PEDOT:PSS-glued MoO3 nanowire network for all-solid-state flexible transparent supercapacitors. Issue 12 (4th May 2021) - Liang, Jie; Sheng, Hongwei; Wang, Qi; Yuan, Jiao; Zhang, Xuetao; Su, Qing; Xie, Erqing; Lan, Wei; Zhang, Chuanfang (John)
Abstract : PEDOT:PSS-glued MoO3 nanowires were anchored on AgNFs network to build all-solid-state flexible transparent supercapacitors with high performances. Abstract : Flexible transparent supercapacitors (FTSCs) are essential for the development of next-generation transparent electronics, however, a significant challenge is to achieve high-areal-capacitance FTSCs without sacrificing optical transparency. Herein, poly(3, 4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)-glued MoO3 nanowires anchored on the Ag nanofiber (AgNF) network are employed as FTSC film electrodes, in which the AgNF network provides primary conducting pathways and guarantees rapid electron transport, while wide-bandgap semiconductor MoO3 nanowires glued by the ultrathin PEDOT:PSS layer provide abundant redox-active sites to store energy. Benefiting from the PEDOT:PSS as the conducting glue to promote the connection at the junctions between AgNFs and MoO3 nanowires, the as-prepared AgNFs/MoO3 /PEDOT:PSS (AMP) film electrode demonstrates a high transmittance (82.8%) and large areal capacitance (15.7 mF cm −2 ), and has outperformed all the transparent conductive films known to date. Even after 11 000 charge/discharge cycles, the capacitance still remains at 92.4% of the initial value. The assembled all-solid-state FTSC device delivers an energy density of 0.623 μW h cm −2, a power density of 40 μW cm −2, and excellent mechanical robustness, implying a great potential in high performance FTSCs.